LUNG-HOMING OF ENDOTHELIAL PROGENITOR CELLS AND ANGIOGENESIS IN ASTHMA: ROLE OF EOSINOPHILS - Sivapalan, Nirooya (My University, 2013)
Asthma involves a systemic element that includes the mobilization and lung-accumulation of bone marrow-derived endothelial progenitor cells (EPC). This traffic may be driven by the stromal cell derived factor-1α (SDF-1α)/CXCR4 axis, where SDF1-α is a potent progenitor cell chemoattractant.
Interfering with EPC lung-accumulation by administering AMD3100, a CXCR4 antagonist, was previously shown to be associated with the modulation of airway angiogenesis and airway hyperresponsiveness. However, since eosinophils express CXCR4, it is unknown whether AMD3100 acted directly on EPC or indirectly through its anti-inflammatory effects on eosinophils.
We investigated the role that eosinophilic inflammation plays in the lung-homing of EPCs and airway angiogenesis in allergic asthmatic response by utilizing eosinophil deficient (PHIL) mice.
Wild-type BALB/c (WT) and PHIL mice underwent a chronic house dust mite (HDM) exposure protocol. Treatment groups were administered AMD3100. Outcome measurements were made 24hrs post final exposure and included: flow cytometry to enumerate lung-extracted EPCs, immunostaining for von Willebrand factor to assess bronchial vascularity, bronchoalveolar lavage for airway inflammation, haematoxylin and eosin stain to enumerate eosinophils, picrosirius red stain to assess collagen deposition, and measurement of airway resistance to increasing intranasal doses of methacholine.
HDM exposed mice had a significant increase in EPC lung accumulation, bronchial vascularity, airway inflammation, collagen deposition and airway hyperresponsiveness (AHR) in both WT and PHIL groups, with some indices at lower levels in PHIL mice. Concurrent treatment with AMD3100 significantly attenuated EPC lung homing, bronchial vascularity, eosinophil numbers in lung tissue and AHR, but not collagen deposition in WT mice. AMD3100 treatment significantly attenuated all indices in PHIL mice.
The findings of this study show that, EPC-driven angiogenesis and the development of AHR in allergic airway responses are independent of eosinophils, the presence of these cells, however, may have a role in worsening of the pathology of allergic airways disease.
Keywords: asthma; angiogenesis; endothelial progenitor cell; stromal-derived factor-1α; eosinophils; house dust mite; Circulatory and Respiratory Physiology; Immune System Diseases; Medical Immunology; Respiratory System; Respiratory Tract Diseases; Circulatory and Respiratory Physiology